EFFICACY OF COW URINE AND PLANT PRODUCTS AGAINST HONEYBEE MITE, VARROA DESTRUCTOR (ANDERSON AND TRUEMAN) IN APIS MELLIFERA (LINNAEUS) COLONIES IN UTTARAKHAND - A NOVEL APPROACH - TIWARI, RUCHIRA; MATHUR , VAIBHAV; BISHT, BRIJESH (The Bioscan, 2014)
The studies to manage the ectoparasitic brood mite, Varroa destructor infestation in the bee colonies of Apis mellifera (L.) at different locations of Uttarakhand were conducted during the years 2012 and 2013 by applying eco-friendly animal origin and plant products. The complied average data of all three apiaries at Dineshpur, Haldwani and Halduchaur revealed that cow urine (desi breed) @ 100%, significantly reduced brood mite infestation (75.60%) with highest mean mite fall (38.00) and sealed worker brood area (SWBA) (1042.00 cm2) followed by cow urine (jersy breed) @ 100% with reduction brood mite infestation, mite fall and SWBA were (75.27%, 37.33 and 991.36 cm2), ajwain powder @ 5g (74.09%, 35.67 and 988.52 cm2) cow urine (holstein breed) @ 100% (71.57%, 33.00 and 974.34 cm2) and neem leaf powder @ 5g (66.59%, 32.33, 892.32 cm2) in comparison to synthetic chemicals i.e. thymol @ 500mg (58.55%, 29.00 and 464.16 cm2) and formic acid @ 5ml (45.35%, 20.33 and 372.44 cm2) and untreated control where reduction in brood mite infestation was (13.33%) and SWBA was (272.44 cm2) after 4 weeks of treatments. It has been concluded that the tested eco-friendly cow urine and plant products were significantly reduced the mite infestation in treated bee colonies with significant increase in mite fall and sealed worker brood area without adversely affected the workers an queen activities in comparison to synthetic chemicals used in A. mellifera colonies. All eco-friendly plant products and cow urine were found significantly superior to untreated control. This was the novel approach to study about the effect of eco-friendly animal origin and plant products as a potential eco- friendly measure for management of mite disease in honeybee colonies in Uttarakhand and which could be suitable alternatives to conventional synthetic chemicals such as thymol, sulphur, apistan, formic acid, dicofol.